PERANCANGAN APLIKASI E-SPK BERBASIS WEB PADA DIVISI MARKETING SUPPORT PT INDOFOOD SUKSES MAKMUR TBK BOGASARI FLOUR MILLS - Yuda, Afri (Fakultas Sains Dan Teknologi Universitas Islam Asyafiiyah, 2025)
The management of Work Order Letters (SPK) at PT Indofood Sukses Makmur Tbk Bogasari Flour Mills Marketing Support Division is manual, causing delays, data errors, and resource inefficiency. This study aims to develop a web-based E-SPK system to automate SPK processes. The Waterfall method was used, covering requirement analysis, design, implementation, and testing. The system was built using PHP (Laravel), Bootstrap, and MySQL. Data were sourced from divisional operational needs, with features including login, SPK data input, PDF generation, Electronic signatures, and CRUD functions. Testing shows E-SPK enhances efficiency, accuracy, and transparency via real-time status tracking. It supports company digitalization and practical IT experience. Future enhancements include certified digital signatures and email document delivery. Keywords: E-SPK, Work Order Letter, Laravel, Web Application, Digitalization